SOCIAL AND ECONOMICS FACTOR IN THE DYNAMICS OF CRIME IN JAPAN - Haruto Saito; Daiki Kobayashi; Zhang Ming (CV. Tirta Pustaka Press, 2025)
This study looks at how social and economic factors have affected crime patterns in Japan over the past 20 years. It focuses on how changes in population, economy, and society have led to more minor crimes by the elderly and more serious crimes by young people. Using a qualitative method and secondary data from official reports and academic sources, the study aims to understand the social and economic reasons behind these crime changes. This study looks at how social and economic factors have affected crime in Japan over the last 20 years. Even though Japan has low crime rates, changes like an aging population and economic problems such as income gaps and job insecurity have caused crime patterns to change. This study uses a qualitative descriptive method with secondary data from crime reports, census data, and academic articles. The data from the last 20 years are analyzed by looking for common themes related to social and economic factors affecting crime. The findings show that more elderly people are involved in minor crimes due to social isolation and financial difficulties. Meanwhile, economic pressure and social breakdown among young people lead to more serious crimes like cybercrime and domestic violence. The Japanese government has made policies to address these issues, but a broader approach that includes social, economic, and psychological aspects is needed for better crime prevention. This study highlights the need to understand crime as a complex social problem to develop lasting and flexible policies that adapt to social changes.